Determinants for the publication of scientific articles in indexed journals: the case of Universidad Nacional Agraria del Perú - Delgado Arenas, Raúl; Delgado Arenas, Antonio Leonardo; Hermitaño Atencio, Bernardo Climaco (Revista General de Información y Documentación, 2021)
Scientific production is a fundamental part of university teaching activity, as part of research and dissemination of scientific knowledge. Scientific production is measured by the number of scientific documents published, such as research articles and books. Due to the importance of the publication of scientific articles for university teaching, the present research was carried out to analyse the determining factors for the publication of articles in journals indexed in Scopus and WoS by professors at the Universidad Nacional Agraria La Molina in Peru. A search was carried out on the website of the National Council for Science, Technology and Innovation of Peru and information was extracted on factors such as: gender, number of researchers, registration as a researcher, academic degree, years of teaching service, level of English, theses advised, research projects and articles published. As a dependent variable, the condition of whether or not they had published articles was used and a multinomial logistic regression was carried out to establish the dependence of this on the factors. The scientific production of teachers is low and only 17.9% are classified as researchers. The determinants of the publication of articles were academic degree, thesis advising and participation in research projects. It is concluded that there is little scientific culture, with teachers mostly with more than 25 years of service and postgraduate studies, with few theses advised, as well as participation in research projects, which influences the low scientific production.
Keywords: Scientific knowledge; Dissemination of knowledge; Scientific publication